The Interplay between Usability and Aesthetics: More Evidence for the "What Is Usable Is Beautiful" Notion. (25th November 2014) - Hamborg, Kai-Christoph; Hülsmann, Julia; Kaspar, Kai
Abstract : With respect to inconsistent findings on the interplay between usability and aesthetics, the current paper aimed to further examine the effect of these variables on perceived qualities of a mobile phone prototype. An experiment with four versions of the prototype varying on two factors, (1) usability (high versus low) and (2) aesthetics (high versus low), was conducted with perceived usability and perceived beauty, as well as hedonic experience and the system's appeal as dependent variables. Participants of the experiment (N = 88 ) were instructed to complete four typical tasks with the prototype before assessing its quality. Results showed that the mobile phone's aesthetics does not affect its perceived usability, either directly or indirectly. Instead, results revealed an effect of usability on perceived beauty, which supports the "what is usable is beautiful" notion instead of "what is beautiful is usable." Furthermore, effects of aesthetics and of usability on hedonic experience in terms of endowing identity and appeal were found, indicating that both instrumental (usability) and noninstrumental (beauty) qualities contribute to a positive user experience.